2021
DOI: 10.1055/a-1366-9656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Venous Thromboembolism or Mortality in Hospitalized COVID-19 Patients

Abstract: Objectives: To identify the prevalence and predictors of VTE or mortality in hospitalized COVID-19 patients. Methods: A retrospective cohort study of adult COVID-19 patients admitted to an integrated health care network in the New York metropolitan region between March 1, 2020 and April 27, 2020. The final analysis included 9407 patients with an overall VTE rate of 2.9% (2.4% in the medical ward and 4.9% in the ICU) and a VTE or mortality rate of 26.1%. Most patients received prophylactic-dose thromboprophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 24 publications
(46 reference statements)
8
74
1
5
Order By: Relevance
“…Further, 17% of our patients on therapeutic anticoagulation received it empirically and for presumed PE without undergoing definitive testing; this may have lowered the precision of our estimates of VTE ( Supplemental Material 6 , www.thejh.org ). Our rates of VTE are comparable to the study of Cohen et al, who also reported overall VTE rate to be 2.9% in 9,407 patients in New York area [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Further, 17% of our patients on therapeutic anticoagulation received it empirically and for presumed PE without undergoing definitive testing; this may have lowered the precision of our estimates of VTE ( Supplemental Material 6 , www.thejh.org ). Our rates of VTE are comparable to the study of Cohen et al, who also reported overall VTE rate to be 2.9% in 9,407 patients in New York area [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…In a large American cohort study of 9407 adult COVID-19 patients, the overall in-hospital venous thromboembolism (VTE) was approximately 3%. The authors concluded that key predictors of VTE or mortality included advanced age, increasing CCI, past history of cardiovascular disease, ICU level of care, and elevated level of D-dimer [35]. In addition, several radiologists tried to differentiate COVID-19 from Influenza and other viral pneumonia on chest CT images [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, D-dimer levels greater than 4 or 6 times the upper limit of normal or elevated SIC scores have been recognized as independent predictors of thrombotic events and poor outcomes (14). Consistent with these findings, multivariate analysis using data from a cohort of 9407 patients with COVID-19 hospitalized at Northwell Health revealed that compared with lower levels, D-dimer levels 4-6 times the upper limit of normal were associated with a 2.1-fold higher risk of VTE or mortality (28). Accordingly, this trial uses inclusion criteria anchored on D-dimers at least 4 times the ULN or an SIC score of 4 or more to ensure enrollment of a high risk population.…”
Section: Accepted Manuscriptmentioning
confidence: 74%